Academic writing for UiTM students (AW4UiTM) / Tengku Intan Suzila T.S. and Mohd Yusri, M.N. - T.S., Tengku Intan Suzila; M.N., Mohd Yusri (2020)
Academic Writing for UITM students (AW4UITM) has been materialized as a part of the open distance learning (ODL) effort. It uses the Facebook social media platform but adapted for the need of the education field. AW4UITM gathers digital based standardized teaching quizzes and videos that are highly anticipated to suit current visual oriented students, mobile and ease of platform used. The AW4UITM has promotional purposes which encourage the learning of academic writing which has always been deemed challenging. AW4UITM was materialized in May 2020. At present, AW4UITM has 91 UITM and non UITM students/FBfriends. The problem that led to AW4UITM is uploaded quizzes and learning videos on Google Classroom cannot induce students' feedbacks. Thus, the objective of AW4UITM is to monitor and gain livelier feedbacks of learning. The use of FB social media platform in this case has elevated information dissemination. Findings suggest that AW4UITM may encourage and ease the learning of academic writing among students.